Effect of a Positive Mindfulness Program on Positive Emotional Development in Final-Year Students: A Pre-Experimental Study in Semarang - Harits, Ajeng Octavia Insani; Harahap, Farida; Asih, Sholeha Tri (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to determine the effect of a positive mindfulness program on increasing positive emotions in final year students. Methodology: This study uses a quantitative approach with an experimental research type. The research design used is a Pre-experimental one group pretest-posttest design. The study was conducted on final year students in Semarang with 18 participants. The determination of research participants used a purposive sampling technique. Data were obtained by filling out the Positive and Negative Affect Schedule (PANAS) and Mindfulness Based Self-Efficacy Revised (MSES-RR) scales before and after being given a positive mindfulness intervention. Main Findings: The results of the hypothesis test using the paired sample t-test obtained a significance value of p <.001 (p <0.05), thus the hypothesis in this study was accepted, this means that the positive mindfulness intervention program significantly influenced in increasing positive mindfulness in final year students with a Cohen's d value or effect size of 0.632 on the PANAS instrument and an effect size of 0.270 on the MSES-R instrument. Novelty/Originality of this study: The novelty of this study lies in its adoption of a positive mindfulness approach, which explicitly aims to cultivate positive emotions. This study will measure the increase in positive emotions directly. Through positive mindfulness, final-year students can view problems more focusedly and objectively, as well as be fully aware of what they are feeling, thereby helping individuals to bring forth positive emotions.